How to identify IgA nephropathy presenting as nephrotic syndrome coexisting with minimal change disease? A 15-year single-center clinicopathological analysis - Yang, Yue; Duan, Lu-xian; Wang, Ying; Zhang, Zheng; Xu, Qian-qian; Zhuo, Li; Li, Wen-ge (Frontiers in Immunology, 2025)
ObjectivesNephrotic syndrome (NS) in IgA nephropathy (IgAN) may indicate concurrent minimal change disease (MCD). This study characterized the IgAN-MCD overlap phenotype using anti-nephrin autoantibodies (IgG co-localization) in NS-IgAN patients, assessing its prevalence and therapeutic implications.MethodsWe conducted a retrospective analysis of 67 biopsy-confirmed NS-IgAN patients (2010-2024) with ≥1-year follow-up. Patients were stratified by treatment response into complete remission (CR, n = 24) and non-remission (NR, n = 26) groups. Renal biopsies were evaluated for anti-nephrin autoantibodies via IgG co-localization and podocyte ultrastructure. Longitudinal data were analyzed using repeated-measures ANOVA with Benjamini-Hochberg correction; time-to-remission was assessed by Kaplan-Meier and Cox regression analyses.ResultsCR patients showed significantly lower baseline serum albumin (18.8 ± 4.0 vs. 24.1 ± 4.2 g/L, P < 0.001) and higher eGFR (101 ± 29 vs. 62 ± 35 mL/min/1.73m², P < 0.001) compared to NR patients. Anti-nephrin IgG co-localization was detected in 54.2% of CR patients but absent in NR patients (P < 0.001). Cox regression identified anti-nephrin positivity as a strong predictor of faster remission (HR: 0.40, 95% CI: 0.17-0.90; P = 0.028). CR patients achieved rapid proteinuria remission (0.1 ± 0.1 vs. 7.0 ± 0.8 g/24h at 1 month, P < 0.001) with significant time×group interactions for proteinuria (P = 0.001) and serum albumin (P = 0.004). An estimated 35.8% of NS-IgAN cases represented IgAN-MCD overlap.ConclusionA significant subset (~36%) of NS-IgAN patients exhibit an IgAN-MCD overlap state identifiable by renal anti-nephrin IgG co-localization, demonstrating MCD-like pathology and excellent corticosteroid response. This biomarker integration can guide personalized therapy, enabling effective short-course treatment for overlap cases while avoiding unnecessary long-term immunosuppression in classic NS-IgAN.